A blinded, randomized clinical trial comparing the efficacy and safety of oclacitinib and ciclosporin for the control of atopic dermatitis in client‐owned dogs. Issue 1 (12th December 2014) - Little, Peter R.; King, Vickie L.; Davis, Kylie R.; Cosgrove, Sallie B.; Stegemann, Michael R.
<x xml:space="preserve">Abstract</x> Background Ciclosporin is approved for the treatment of atopic dermatitis (AD) in dogs and has been shown to be safe and effective. Placebo‐controlled studies suggest that oclacitinib is a safe and effective alternative therapy. Hypothesis/Objectives To evaluate the efficacy and safety of oclacitinib, in comparison to ciclosporin, for the control of AD in a blinded, randomized clinical trial, incorporating a noninferiority test at day 28. Animals A total of 226 client‐owned dogs with a history of AD from eight sites were enrolled. Methods Enrolled animals were randomized to receive oral oclacitinib (0.4–0.6 mg/kg twice daily for 14 days, then once daily) or oral ciclosporin (3.2–6.6 mg/kg once daily) for 12 weeks. Owners assessed pruritus using an enhanced visual analog scale (VAS), and veterinarians assessed dermatitis using the Canine Atopic Dermatitis Extent and Severity Index (CADESI)‐02. Results On days 1, 2, 7, 14, 28, 56 and 84, the percentage reduction from baseline for owner‐assessed pruritus changed from 25.6 to 61.0% in the oclacitinib group compared with 6.5 to 61.5% in the ciclosporin group; differences were significant at all time points up to day 28. On day 56, ciclosporin‐treated dogs showed a similar decrease in pruritus to oclacitinib‐treated dogs. On day 14, the percentage reduction from baseline CADESI‐02 was significantly greater in the oclacitinib group (58.7%) than in the ciclosporin group (43.0%). Three times as many adverse events attributed to gastrointestinal signs were reported in the ciclosporin group compared with the oclacitinib group. Conclusions and clinical importance In this study of treatment for canine AD, oclacitinib had a faster onset of action and a lower frequency of gastrointestinal side effects compared with ciclosporin.